(untitled) (EAAE Joint Publishings, 2026)
To address global challenges like climate change, pollution, and social inequality, we must broaden our thinking and train the next generation of leaders—young students. Introducing bamboo as a building material through architecture education is one way to explore its potential and promote sustainable practices. This paper focuses on the role of architectural education in teaching aspiring students about bamboo materials for sustainable community development, through a participatory bamboo installation project. In this initiative, a group of students worked in five teams, each consisting of five members, to design structures using bamboo—a sustainable, indigenous material. Over time, their designs evolved during review sessions, from simple to complex, and from basic forms to more creative, student-generated structures. They moved from small-scale models to larger ones, eventually constructing a real-scale structure. These hands-on, interactive exercises fostered great enthusiasm among the students and professors, moving beyond theoretical learning. Workshops, talks, and presentations were held to explore the stability of skeletal systems in creative ways. The newly built models, featuring different joists, knots, weaving patterns, and construction techniques, allowed the students to test their theoretical ideas. The tactile qualities and construction potential of bamboo and other locally available materials became evident, highlighting their practicality. This study also aims to identify gaps in research on bamboo as a sustainable material for community development. While bamboo has been explored in some areas, it remains underinvestigated in others. By considering bamboo as an eco-friendly building material, this project aligns with the low-carbon movement and encourages young leaders to adopt sustainable practices. The practical experience provided a deeper understanding of these issues than theoretical lectures ever could, making the students and instructors more aware and knowledgeable about bamboo’s potential for sustainable architecture.